SCIENTIFIC AND THEORETICAL FOUNDATIONS OF THE AUTHOR'S CONCEPT (Scientific journal of the Fergana State University, 2025)
This article examines the scientific and theoretical foundations of the terms “author” and “author's concept” in literary studies. The author's concept is defined as the author's artistic, scientific, and creative program, consisting of several components. The essence of these components and the interpretation of the author's concept as an initial scientific problem are presented.